Exploring the relationship between dimensions of quality management practices and business performance. (23rd September 2019) - Singh, Deepinder; Singh, Harwinder; Singh, Jagwinder; Kumar, Raman
Quality management practices (QMP) can be either explorative or exploitative, and these can benefit organisation with both orientations. In this research work, an attempt has been made to explore the dimension of QMP with respect to business performance. A path model is developed which exhibit the relationship between QMP and business performance. The SPSS AMOS 21 software package was used to perform confirmatory factor analysis. The second order confirmatory factor analysis was used to test the considered six hypotheses. The finding showed that top management support (TMS), supplier relationship (SR), workforce commitment (WC), people management (PM), workplace organisation (WO) are directly related to business performance. Moreover, leadership is not directly associated with business performance. The outcome of this study offers theoretical as well as practical managerial implication to improve business performance.